Valuing elite sport success using the contingent valuation method: A transnational study. Issue 3 (June 2020) - Funahashi, Hiroaki; Shibli, Simon; Sotiriadou, Popi; Mäkinen, Jarmo; Dijk, Bake; De Bosscher, Veerle
Highlights: The contingent valuation method was used to value elite sport success on a transnational basis. Samples of adults in five countries were asked for their willingness to pay for a 'high-performance sport fund' in order to avoid a decline in medal performance at the next Summer Olympic Games. Respondents in the more successful medal winning countries reported higher willingness to pay than those in the relatively less successful countries. In line with welfare economics theory, more medals won appears to be linked with more utility among individuals. Abstract: This study presents an application of the contingent valuation method for valuing medal winning success on a transnational basis to test whether more medals won equates to more utility. To achieve this aim, a research project was set up in five countries: Belgium, Finland, Japan, the Netherlands, and the United Kingdom. Respondents were asked to state their willingness to pay to avoid a large-scale reduction in government funding for elite sport, resulting in a 50% reduction in medals won at the Tokyo 2020 Olympics. Results show that willingness to pay for avoiding reduced medal winning performance differs significantly between countries with the more successful countries reporting higher willingness to pay values than the relatively less successful countries. This finding indicates that more medals won appears to be linked with more utility. The validity tests on the regression models were generally consistent with the theoretical expectations. Implications are discussed in terms of how governments can promote elite sport development while being conscious of the public's acceptability of such investment.